Gene Expression of Carbapenemase-Encoding Genes in Multi-Drug Resistant Staphylococcus aureus from Clinical Sources - Sara Saad Alnejadi; Ahmed Hamad Saleh (Journal of Medical Genetics and Clinical Biology, 2024)
The emergence of multi-drug resistant (MDR) Staphylococcus aureus strains, particularly those expressing carbapenemase genes, poses a significant challenge in clinical settings. This study investigates the prevalence and expression profiles of carbapenemase genes (blaVIM, blaOXA-143, blaGES, blaOXA-23, and blaOXA-24) in S. aureus isolates from burn and wound patients in Tehran hospitals. A cross-sectional study was conducted using 100 S. aureus samples, which underwent biochemical testing for identification and antibiotic susceptibility testing. Gene expression analysis was performed using real-time PCR, and the results were analyzed with GRAPH PAD PRISM software. The study highlights the importance of understanding the molecular mechanisms of antibiotic resistance in S. aureus and contributes to the development of effective treatment strategies against MDR infections.